1997
DOI: 10.1002/(sici)1097-0010(199706)74:2<216::aid-jsfa791>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The Potassium, Sodium, Magnesium, Calcium and Phosphate Nutrition of Sugarbeet (Beta vulgaris) Grown on Soils Containing Incorporated Straw

Abstract: Between 1990 and 1992, a series of three experiments compared the effects of incorporating or removing straw from a total of five preceding cereal crops on the nutrient concentration, uptake and processing quality of sugarbeet. Incorporated straw increased K concentrations in tops and roots and increased total K uptake by c 40 kg ha‐1. Conversely, incorporated straw reduced Na concentrations and reduced total Na uptake by c 10 kg ha‐1. Straw incorporation had little effect on root processing quality, because w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Eghball et al (2002) stated that more than 55 % of the organically applied Mg is plant available. Allison et al (1997) reported that in sugar beet grown on soils where straw was incorporated the uptake of Mg but also of phosphorus (P) and Ca was not significantly affected, whereas the K uptake was increased by about 40 kgha −1…”
Section: Use Of Mg Efficient Cultivarsmentioning
confidence: 99%
“…Eghball et al (2002) stated that more than 55 % of the organically applied Mg is plant available. Allison et al (1997) reported that in sugar beet grown on soils where straw was incorporated the uptake of Mg but also of phosphorus (P) and Ca was not significantly affected, whereas the K uptake was increased by about 40 kgha −1…”
Section: Use Of Mg Efficient Cultivarsmentioning
confidence: 99%
“…The content of nitrogen and minerals in sugar beet has been the subject of numerous experiments in which their variability due to fertilizing, tillage, varieties and weather conditions was observed. The authors have demonstrated proven relationship between the level of concentration of mineral nitrogen and macronutrients and certain features of technological value of roots, especially sugar and molasses forming substances -α-amino nitrogen and sodium and potassium cations (ALLISON et al 1997, S£OWIÑSKI et al 1997, BAR£ÓG et al 2002, BAR£ÓG, GRZEBISZ 2004, DIATTA 2004, PROOEBA--BIA£CZYK 2003, 2005a,b, PROOEBA-BIA£CZYK, MYDLARSKI 2001.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to K, there is strong evidence of the positive benefits of good K fertility management on disease resistance, including that to AgSS (Williams and Smith, 2001). Evidence has clearly shown the positive residual impact of straw incorporation on the K fertility status of agricultural soils (Cox and Uribe, 1992;Allison et al, 1997;Wihardjaka et al, 1999;Dierolf and Yost, 2000). In particular, straw management plays a critical role in the K fertility status of rice soils since it contains about 80% of the above ground plant K (Dobermann et al, 1996(Dobermann et al, , 1998Dobermann and Fairhurst, 2000) and its removal has been cited as the major culprit of K deficiencies in irrigated rice fields throughout Asia (De Datta, 1981;Gill and Kamprath, 1990;Dobermann et al, 1998).…”
mentioning
confidence: 99%